Posztszocialista átalakulás Közép- és Kelet-Európa rurális társadalmaiban (Szociológiai Szemle, 2024)
The main topic of our paper is the emergence of new structures within rural society in six countries (Russia, Hungary, Poland, Slovakia, Czech Republic, and Bulgaria) and the development of the institutional environment of these transformation. In the first chapter we present some theories on the nature of rural-urban duality in redistributive state socialism. Thereafter we formulate two hypotheses on wage distribution and unemployment that we see the major factors of the new subjugation of rural people. The third chapter contains the data analysis and presents regional models of transformation.We stated that the differentiation of wages was less influenced by the rural-urban divide, the wages of rural people are increasingly shaped by the market mechanisms in countries that have gone farthest in building a market economy. At the same time new variants of income inequalities have evolved, each determined by employment. In countries where the rural-urban differences have been least related to the differentiation of wages, unemployment and other forms of employment have become the primarily decisive factors of the new type of inequalities.